Izhodišča primernosti habitatov nekaterih kvalifikacijskih vrst ptic v gozdovih - Perušek, Mirko (Gozdarski vestnik, 2006)
The article presents some fundamental factors which influence protected bird species included in Natura 2000 and presents some interspecific interactions and issues which may influence the distribution of protected species in forests. Minimum criteria for the conservation of forest habitats of forest owls and grouse species are given. The author maintains that protected speciesare inadequately included in forest management planning. In everyday forest work foresters should devote more attention to new nature conservation issues.
Keywords: habitati; forest; gozd; Natura 2000; ptice; bird